(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
A series of novel 3-(((1H-benzo[d]imidazol-2-yl)methyl)thio)-5H-[1,2,4]triazino[5,6-b]indole derivatives (3a-3j) were synthesized by reacting different substituted 5H-[1,2,4]triazino[5,6-b]indole-3-thiols with substituted (2-chloromethyl)-1H-benzo(d)imidazoles in the presence of KOH and water in good yields. The structures of the newly synthesized compounds were confirmed by spectroscopic techniques such as 1H-NMR, 13C-NMR, IR and mass spectrometry. The in vitro antitubercular activity of the synthesized compounds was evaluated against Mycobacterium tuberculosis (Mtb) H37Rv (ATCC 27294) using MABA (Microplate Alamar Blue Assay) method. Compounds 3b, 3c, and 3i showed good antitubercular activity against Mtb with MIC value of 6.25±0.00 μg/ml. Also, the in vitro antimicrobial activities of the compounds were evaluated against various bacterial and fungal strains using the two-fold serial dilution technique and most of the compounds exhibited moderate activities with MIC values in the range of 63.33±1.44 to >500